Efficiency and Reliability Performance's of the Bioinformatics Resource Portal - Edy Budiman; Haeruddin Haeruddin; Andi Tejawati (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This paper discusses the resource portal of the analysis of the Borneo's Biodiversity Information System (BBIS) from the point of view of the characteristics of efficiency and reliability performance. Data collection methods and tools use the observation approach that simulates 100 simultaneous users, logging every 10 seconds between random clicks on the URL site. Efficiency testing results that measured 27 recommendations from PageSpeed measuring instruments and 19 recommendation parameters from YSlow, obtained average scores on grade A. However, there were still 6 parameters related to system resource issues with grade F scores, and these parameters were the significant effect the reliability value. Reliability test results referring to Jacob Nelson's equation approaches and Standard Telcordia reference. The result shows that the value of R = 0.988967 or the percentage of the reliability value is 98.89% and r = 0.011 or the error rate is 1.1%. and the user threshold test results are found when the number increases to 500 users. The success of efficiency testing parameters significantly affects the percentage of performance reliability.